Hubungan antara Regulasi Diri dalam Belajar dengan Grit pada Mahasiswa Program Studi Bimbingan dan Konseling Universitas PGRI Semarang - Dewi Sekar Millati; Dini Rakhmawati; Desi Maulia (Journal on Education, 2024)
This research is motivated by learning habits taken from the answers to the Final Semester Examination on January 18, 2024, 2023 guidance and counseling students said that their learning habits still need adjustment in terms of managing time for learning and other activities. Self-regulation in learning and grit is considered important to understand how a person persists in a goal. The purpose of this study was to determine the relationship between self-regulation in learning with grit in guidance and counseling students at PGRI Semarang University. This type of research is quantitative with a correlational research design. The research data population amounted to 125 students which included 3A class as many as 30, 3B as many as 34, 3C as many as 29, and 3D as many as 32. While the sample was 29 from class 3C which was taken with saturated sample technique. The data collection tools used are psychological scales of self-regulation in learning and grit. Based on the Pearson product moment correlation test, the correlation value r count is 0.226. While the r table value for a sample size of 96 with a significance level of 5% is obtained at 0.201. Therefore, the value of r count 0.226 > r table 0.201, it can be concluded that there is a significant relationship between self-regulation in learning with grit in guidance and counseling students at PGRI Semarang University.